2013
DOI: 10.1158/1535-7163.mct-12-0926
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of OATP1B-Type Transporter Function Alters Cellular Uptake and Disposition of Platinum Chemotherapeutics

Abstract: Expression of the human organic anion transporting polypeptides OATP1B1 and OATP1B3 have been previously believed to be restricted to hepatocytes. Here we demonstrate that the gene encoding OATP1B3, but not OATP1B1, is abundantly expressed in multiple human solid tumors that include hepatocellular, lung, and ovarian carcinomas. Surprisingly, OATP1B3 expression in a panel of 60 human tumor cell lines was linked with sensitivity to multiple cytotoxic agents, including the platinum anticancer drugs cisplatin, car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
51
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 59 publications
(55 citation statements)
references
References 38 publications
4
51
0
Order By: Relevance
“…Previous microarray analysis showed that expression of transporter genes in the kidneys of wild-type and Oatp1b Ϫ/Ϫ mice is similar with the exception of Slc14a2, which was increased in Oatp1b Ϫ/Ϫ mice (17). Because Slc14a2 transcript encodes urea transporter A (UTA), a protein that has been shown to mediate cellular entry of hydroxyurea (30), real-time analysis was conducted to evaluate the relative expression of this gene in wild-type and Oatp1b Ϫ/Ϫ mice.…”
Section: Discussionmentioning
confidence: 94%
“…Previous microarray analysis showed that expression of transporter genes in the kidneys of wild-type and Oatp1b Ϫ/Ϫ mice is similar with the exception of Slc14a2, which was increased in Oatp1b Ϫ/Ϫ mice (17). Because Slc14a2 transcript encodes urea transporter A (UTA), a protein that has been shown to mediate cellular entry of hydroxyurea (30), real-time analysis was conducted to evaluate the relative expression of this gene in wild-type and Oatp1b Ϫ/Ϫ mice.…”
Section: Discussionmentioning
confidence: 94%
“…Although formal drug interaction studies have not been performed to date with nab-paclitaxel, our present findings strongly suggest that drug-drug interactions at the level of hepatocellular uptake mechanisms would be exacerbated with a formulation like nab-paclitaxel. Conversely, CrEL may act as a perpetrator in known pharmacokinetic interactions involving other OATP1B substrates co-administered with paclitaxel [reviewed in (4)], such as etoposide (43), docetaxel (44), oxaliplatin (45), and SN-38 (46). …”
Section: Discussionmentioning
confidence: 99%
“…Thus, various family members of the ABC transporter family as well as SLC and solute carrier organic anion transporters are expressed in the lung (Bosquillon, 2010). The solute carrier organic anion transporter OATP1B3 is expressed in normal lung as well as in solid lung tumors, and was shown to correlate with disposition and toxicity of platinum cancer chemotherapy drugs (Lancaster et al, 2013).…”
Section: Pulmonary Metabolism Of Resveratrol: In Vitro and In Vivomentioning
confidence: 99%